(untitled) (Journal of the College of Basic Education, 2026)
The research aimed to identify the role of artificial intelligence in improving sports marketing strategies in Iraqi sports clubs by constructing a scale for artificial intelligence and a scale for sports marketing strategies, as well as examining the relationship between them. The researcher adopted the descriptive approach using the survey method due to its suitability to the nature of the research problem.The research sample consisted of members of the administrative bodies in Iraqi Premier League sports clubs, totaling (180) members, distributed into a pilot sample, a construction sample, and an application sample. The researcher developed the research instruments by formulating a set of items according to a five-point Likert scale, in line with the nature of the research population. After completing the scientific procedures, the validity of the two scales was verified using construct validity through discriminatory power and internal consistency, while reliability was confirmed using Cronbach’s alpha coefficient. The results indicated that the two scales have high levels of validity and reliability.After applying the scales to the research sample, the results revealed a statistically significant relationship between artificial intelligence and sports marketing strategies, indicating that the use of artificial intelligence contributes to improving the efficiency and effectiveness of sports marketing strategies in Iraqi sports clubs. In light of these findings, the researcher recommends that Iraqi sports clubs adopt artificial intelligence technologies, develop their technological infrastructure, and enhance staff capabilities to improve marketing performance and achieve sustainable competitive advantage.